Pendampingan Peningkatan Kompetensi Menggunakan Quizizz Sebagai Asesmen Digital Bagi Guru SMA N 2 Bayang - Lisa Candra Sari; Martin Kustanti; Rezki Amelia; Novrianti (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
Abstract. This assistance aims to increase competence in using Quizzizz as a digital assessment for teachers. The method used in this mentoring is the service learning method which follows three stages, namely "preparation stage, serving stage, and reflection stage." The activity took place over 1 meeting with the material being assistance in using the Quizizz application as a digital assessment. The object of this research is the teacher at SMA N 2 Bayang. The results of this assistance show that (1) quizizz is very easy for teachers to use in class and outside of class, (2) quizizz helps teachers prepare questions or assignments to evaluate students' understanding of the material that has been taught, (3) students cannot copy each other , because the questions displayed on Quizizz are randomized, (4) helps teachers analyze student learning outcomes, because Quiziz provides data and statistics about students' work results directly, and (5) makes it easier for teachers to provide homework. So it can be concluded that this mentoring activity is useful for increasing competence in using Quizzizz as a digital assessment for teachers.